Pengaruh Penguasaan Mufradāt terhadap Kemampuan Insyā’ Mahasiswa di Perguruan Tinggi - Kasmiati, Kasmiati; Masbukin, Masbukin; Hendri, Muspika (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
department of the state Islamic University Sultan Syarif Kasim Riau which is presented in the form of Insyā’ 1, Insyā’ 2, and Insyā’ 3 which must be taken by every student. To support learning insyā, students have been provided with mufradāt treasury either through supporting courses such as al-arabiyah al-mukatsafah, or through the obligation to memorize mufradāt which is imposed on students. However, mufrodāt treasure and memorizing it has not made a positive contribution to the student’s abilities. This research is quantitative correlation research because the aim of this research is to find out whether there is an influence of mastery of mufrodāt on the ability of Insyā’ in Arabic Language Education students at the State Islamic University of Sultan Syarif Kasim Riau. This research used a test, questionnaires, and documentation for getting data. To analyze the data, researchers used the reliability and validity test, normality test, and linear regression test. From the results of this research, it can be seen that Sig. Count 0,0smallerer than 0,05 and t count bigger 22,572 than t table 1,672. it can be concluded that vocabulary mastery has a significant effect on Insyā’s ility. It shows that if students' mastery of mufradāt is better, then their abilities will be better too in writing Insyā’.